PARTIAL REPLACEMENT OF CONCENTRATE BY OF IPOMEA BATATAS LEAVES IMPROVES LITTER SIZE AND SURVIVAL OF YOUNG RABBITS ORYCTOLAGUS CUNICULUS - OTCHOUMOU, Kraidy Athanase; WOGNIN, Légbé Marie Flavienne Raïssa; YAO, Konan Franck; NIAMKÉ, Sébastien (International Journal of Research -GRANTHAALAYAH, 2020)
This study was conducted to evaluate the influence of use of Ipomea batatas leaves in the feeding of breeding rabbits. To this end, 28 rabbits does (3.2 kg to 3.5 kg), divided into 2 batches (100% concentrate and 50% concentrate supplemented with 50% Ipomea batatas leaves) have been used. The pregnancy rates were 100% identical. No difference (P> 0.05) was noted between the average feed intake of pregnant rabbits before the farrowing. This parameter was higher in rabbits fed 50% concentrate supplemented with 50% Ipomea batatas leaves after births. The mean litter size of the batches fed the mixture feed was (7.66 rabbits / dam) higher (P <0.05) than that of the 100% concentrate lot (6.85 rabbits / dam). At birth, the mean weight of the rabbits in the 100% concentrated lot (48.29g) was significantly higher (P <0.05) than that of 50% concentrate supplemented with 50% Ipomea batatas leaves (47.74). The rabbits of the 50% concentrate lot supplemented with Ipomea batatas leaves had a survival rate (85.71%) higher than those of the 100% concentrate batch (74.50) at weaning.